A study on the trends and patterns of intestinal obstruction and surgical outcome based on APACHE score II in a tertiary care centre - Sarma, Himangsu; Kudari, Ashwinikumar (International Surgery Journal, 2021)
Background: One of the most common intra-abdominal problems faced by general surgeons in their practice remains bowel obstruction. It is important to identify and analyse the clinical presentation and etiology of patients with acute intestinal obstruction. With its multiple etiologies, intestinal obstruction of either the small or large bowel continues to be a major cause of morbidity and mortality. Methods: An observational study was carried out at Narayana Hrudayalaya Hospital, Bangalore between July 2016 and June 2019 involving 190 patients, after approval from Institutional ethics Committee. Predicted mortality rates were calculated using the APACHE II scoring system by linear analysis method. It was then compared with the actual outcomes. Univariate and multivariate analysis was carried to analyze the collected data. Results: The commonest cause in this study was postoperative adhesions [82 patients (43.2%)]. Frequency of mortality in our study was 7.9%. ROC curve analysis to predict the mortality using APACHE score showed sensitivity (80%), specificity (81.14%) and AUROC=0.796. P value was <0.001 which is highly significant. A positive correlation was found between deaths and complications with higher APACHE scores. Conclusions: Successful treatment of acute intestinal obstruction depends upon early diagnosis, skilful management and treating the pathological effects of the obstruction just as much as the cause itself. The APACHE II score allows for direct comparison between the observed and expected adverse outcome rates. They can also be used to determine prognosis and help family members make informed decisions about the aggressiveness of care.